Size quantization in metal films - Nedorezov, S.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Quantum size effect, predicted by I.M. Lifshits and A.M. Kosevich [Izv. Akad. Nauk SSSR, seriya fiz. 19, 395 (1955)], was investigates in a many works. In the basis of analysis of quantum size oscillations of thermodynamics and kinetic characteristics of metal films lies the quasiclassical quantization of component of momentum for isotropy model and quantization [S.S. Nedorezov, Zh. Eksp. Teor. Fiz. 51, 868 (1966) [Sov.Phys.-JETF 24, 578 (1967)]] of chord of constant-energy surface in the case of anisotropy energetic spectrum. In the given work the research of quantum size levels of energy of electrons in metal films is carried out by the method of J.M. Luttinger–W.Kohn. The exact conditions of size quantization are got.